2016
DOI: 10.1111/jam.13122
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the growth of Escherichia coli O157:H7 and Salmonella in spinach, lettuce, parsley and chard extracts at different storage temperatures

Abstract: Finally, these results can be used as basis to establish risk rankings of pathogens and leafy vegetable matrices with relation to their potential growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previous research has indicated storage of vegetables at ambient conditions allowed for rapid pathogen growth (Hoelzer et al, 2012;Posada-Izquierdo et al, 2016;Mishra et al, 2017). As compared to results from 15°C-stored samples, UG and GPNs treatments yielded non-detectable numbers of E. coli O157:H7.…”
Section: Experimental Replication and Data Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…Previous research has indicated storage of vegetables at ambient conditions allowed for rapid pathogen growth (Hoelzer et al, 2012;Posada-Izquierdo et al, 2016;Mishra et al, 2017). As compared to results from 15°C-stored samples, UG and GPNs treatments yielded non-detectable numbers of E. coli O157:H7.…”
Section: Experimental Replication and Data Analysismentioning
confidence: 80%
“…Recent research describing the growth of both E. coli O157:H7 and Salmonella on spinach indicated increased growth rates of both organisms on the produce commodity when transitioned from refrigeration (5°C) to elevated/abusive storage temperatures, with lag phases of at least 10 h when ambient temperature was ≤21°C (Mishra et al, 2017). Research conducted on presterilized spinach extract indicated similar trends, with more rapid growth occurring when spinach was held at 16 or 20°C versus 8 or 10°C (Posada-Izquierdo et al, 2016). The FDA recommends the preservation of refrigeration conditions for storage of fresh produce during postharvest handling to prevent/slow growth of microbial pathogens (FDA, 2009(FDA, , 2013.…”
Section: Experimental Replication and Data Analysismentioning
confidence: 95%
“…Similar results were also seen with the other leaf juices (data not shown), all of which produced similar growth enhancement at 2%, which we then adopted as our standard salad juice addition concentration. A recent study by Posada-Izquierdo et al (27) also examined the growth kinetics of Salmonella in leafy salad extracts (chard, iceberg lettuce, parsley, and spinach). Those authors used much higher levels (33.3% [vol/vol]) of leaf juice in their growth analyses and found growth rates lower than those that we report here.…”
Section: Resultsmentioning
confidence: 99%
“…from cut surfaces. A number of studies show growth of food-borne bacteria on plant extracts during the production process (35, 55, 56) and growth potential for E. coli O157:H7 has been evaluated in water (70). Here, maximum growth rates in plant extracts were strongly influenced by the plant tissue type and species, as well as the E. coli isolate tested and overlaid by temperature-dependent effects.…”
Section: Discussionmentioning
confidence: 99%